Implementation of Android-Based Dyslexia Therapy and Verbal Dyslexia Therapy for Improving Reading Ability in Dyslexic Children - Sri Respati Andamari; Ulfa Amalia (Psikologia : Jurnal Psikologi, 2017)
This research aims to compare the effectivity of therapy for dyslexia syndrome. Recent research shows that Android-app based therapy is more effective to increase reading ability in children with dyslexia than other, named verbal therapy. Quasy experimental with randomized control group pre and posttest design is used. 20 children with dyslexia are included as research participant and divided into two groups, control-group and experiment-group. Reading ability test is used as measurement tool. Data analyzed with Mann-Whitney U test. Data analysis result shows that android-app based therapy is more effective to elevate reading ability in children with dyslexia.